Naming Characters in Thai Children’s Narratives: a Developmental Perspective - Rungrojsuwan, Sorabud (Journal of Letters, 2019)
The present study aims at investigating the referential forms used in naming narrative characters by Thai children and examining the developmental path of Thai children in character naming. Data from 40 narratives by 4, 6, 9 and 11-year-old children collected by Zlatev and Yangklang (2018) were used. Classified by the number of free morphemes, findings show that two types of referential forms are used: single and combined units. Single-unit forms can be nouns and pronouns, while combined units include two and three-unit combinations with various internal structures. It was found that older groups of children produced more combined-unit referential forms than single-unit ones. This implies the order of acquisition for single units is (COMMON NOUNS > PRONOUNS > PROPER NOUNS) and combined units (N+MOD > N+Det > N+POSS+N/Pron > N+Rel CL.)